Evaluating the Use of Linear Mixed‐Effect Models for Inference of the Concentration‐QTc Slope Estimate as a Surrogate for a Biological QTc Model. (28th January 2015) - Huh, Y; Hutmacher, MM
Abstract : In concentration‐QTc modeling, oscillatory functions have been used to characterize biological rhythms in QTc profiles. Fitting such functions is not always feasible because it requires sufficient electrocardiograph sampling. In this study, drug concentration and QTc data were simulated using a published biological QTc model (oscillatory functions). Then, linear mixed‐effect models and the biological model were fitted and evaluated in terms of biases, precisions, and qualities of inferences. The simpler linear mixed‐effect model with day and time as a factor variables provided similar accuracy of the concentration‐QTc slope estimates to the complex biological model and was able to accurately predict the drug‐induced QTc prolongation with less than 1 ms bias, despite its empirical nature to account for biological rhythm. The current study may guide a concentration‐QTc modeling strategy that can be easily prespecified, does not suffer from poor convergence, and achieves little bias in drug‐induced QTc estimates. CPT Pharmacometrics Syst. Pharmacol. (2015) 4, 1–9; doi:10.1002/psp4.14 ; published online on 29 January 2015.